Product Market Reforms and Unemployment in Europe - Hans Gersbach; Achim Schniewind (Institute for the Study of Labor (IZA), 2001)
In this paper we study how promoting product market competition by reducing mark-ups or by increasing productivity are able to complement labor market reforms. We use a simple general equilibrium model with different types of labor. The bottom-line of the paper is that product market reforms will help to reduce aggregate unemployment under many circumstances even though sectoral unemployment may increase. We also highlight that the mobility of high-skilled workers and the distribution of unemployment across sectors determine whether productivity improvements in one sector affect aggregate unemployment positively or negatively.
Keywords: E24; J60; D58; L13; 330; Product market competition; unemployment; mobility of labor force; political support for reforms; Marktmacht; Deregulierung; Wettbewerb; Beschäftigungseffekt; Allgemeines Gleichgewicht; Arbeitsmobilität; Arbeitslosigkeit; Theorie